Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fmed.2021.684389
|View full text |Cite
|
Sign up to set email alerts
|

Synovial Fibrosis Involvement in Osteoarthritis

Abstract: Bone changes have always been the focus of research on osteoarthritis, but the number of studies on synovitis has increased only over the last 10 years. Our current understanding is that the mechanism of osteoarthritis involves all the tissues that make up the joints, including nerve sprouting, pannus formation, and extracellular matrix environmental changes in the synovium. These factors together determine synovial fibrosis and may be closely associated with the clinical symptoms of pain, hyperalgesia, and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 88 publications
1
38
0
Order By: Relevance
“…Previously, it has been shown that GLS1 inhibition reduces the proliferation of RA synovial fibroblasts, and in vivo reduces joint swelling in a murine model of RA [ 20 ]. Furthermore, in myofibroblasts, GLS1 inhibition reduced ECM production [ 33 , 34 ], a feature of synovial fibrosis in both OA [ 35 , 36 , 37 ] and RA [ 38 ] disease. Importantly, our identification of glutamine–glutamate metabolism as a clinical feature that is enriched in obese OA patient synovial fluid (a patient cohort that exhibits greater levels of inflammatory cytokines), which suggests that targeting this particular metabolic pathway will be of clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been shown that GLS1 inhibition reduces the proliferation of RA synovial fibroblasts, and in vivo reduces joint swelling in a murine model of RA [ 20 ]. Furthermore, in myofibroblasts, GLS1 inhibition reduced ECM production [ 33 , 34 ], a feature of synovial fibrosis in both OA [ 35 , 36 , 37 ] and RA [ 38 ] disease. Importantly, our identification of glutamine–glutamate metabolism as a clinical feature that is enriched in obese OA patient synovial fluid (a patient cohort that exhibits greater levels of inflammatory cytokines), which suggests that targeting this particular metabolic pathway will be of clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…When IL-1β and TNF-α bind to their receptors, an inflammatory signaling cascade is activated, which enhances inflammation and catabolism by increasing the expression of adhesion molecules [ 12 ]. The increased synthesis of cytokines, as well as increased expression of MMP’s family enzymes, can result in ECM degradation [ 13 ]. IL-1β associates with Th17 and NK22 cells for neutrophils recruitment into the tissue, which helps to promote OA [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Synovitis associated with joint injury can promote synovial angiogenesis, which in turn accelerates inflammation and leads to synovial fibrosis (Zhang et al, 2021). At six weeks post-surgery, morphological signs of synovitis were prominent in knee joints that underwent surgery.…”
Section: Resultsmentioning
confidence: 99%